PEDAGOGICAL POTENTIAL OF FLASHCARDS AND CREATIVE GAMES IN LOW-TECH EDUCATIONAL CONTEXTS - Ne’matova Muhlisa Naim qizi; Khaydarova Shoira (TADQIQOTLAR, 2026)
Abstract: This paper examines the pedagogical applications of using flashcards and creative game activities in classrooms where there are limited technical devices. Technical devices are rare in many learning institutions, particularly in developing countries, where language learning becomes a challenge. This paper examines the methodological applications of using creative game activities, as well as flashcards, in improving student motivation, participation, and academic performance. The relevance of using creative game activities, as well as flashcards, in language learning as an approach that does not require technical devices is discussed in this article.